WELDING OF STRUCTURES IN A CARBON DIOXIDE ENVIRONMENT WITH THE ADDITION OF OXYGEN (CO2 + O2) - Juraev Abdullajon Ibragimovich (Bright Mind Publishing, 2025)
This article examines the technological features of welding structures in a carbon dioxide (CO2) environment with the addition of oxygen (O2). The advantages and disadvantages of this welding method, the influence of various parameters on the quality of the welded joint, and recommendations for choosing the optimal gas mixture ratio are highlighted. Special attention is paid to the application of this method in mechanical engineering, construction, and other industries.
Keywords: Welding, carbon dioxide, oxygen, gas mixture, arc welding, weld quality, welding mode, protective environment.